2012
DOI: 10.1002/ajh.23305
|View full text |Cite
|
Sign up to set email alerts
|

The effect of whole body vibration therapy on bone density in patients with thalassemia: A pilot study

Abstract: Patients with thalassemia (Thal) have low bone mass which can lead to fracture and decreased quality of life. There are no noninvasive anabolic therapies available to improve bone health in Thal. A longitudinal cross-over pilot trial was conducted to evaluate the effectiveness of low magnitude whole body vibration (WBV) therapy on bone in 18 patients with Thal (9 adults, 10 male, 22.1 ± 10.7 years). Subjects were asked to stand on a vibrating platform (30 Hz, 0.3 g) for 20 min/day for 6 months. Areal bone mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Thal subjects and controls were asked to wear an ActiGraph (GT3X) accelerometer for week-long intervals, which measured their physical activity frequency and intensity. Twenty of the Thal patients included herein were also enrolled in a randomized trial testing the effect of vibration therapy on bone health 23 . …”
Section: Methodsmentioning
confidence: 99%
“…Thal subjects and controls were asked to wear an ActiGraph (GT3X) accelerometer for week-long intervals, which measured their physical activity frequency and intensity. Twenty of the Thal patients included herein were also enrolled in a randomized trial testing the effect of vibration therapy on bone health 23 . …”
Section: Methodsmentioning
confidence: 99%
“…Peak strains generated by LMS are on the order of approximately 1–2 micro strain (με) while cell responses linked to HMS are usually applied at ≥10,000 με , suggesting that substrate deformation does not contribute to the LMS response. Current literature addressing how cells sense vibration is focused on computational analyses or correlations that do not directly speak to the mechanisms responsible for the cell response to vibration ; indeed research has been largely limited to functional outcome assays describing cell osteogenesis, adipogenesis, proliferation, or tissue/organism level response .…”
Section: Introductionmentioning
confidence: 99%
“…Single studies exist in hematological diseases such as thalassemia and hemophilia. Fung et al [34] found that WBV increased total body BMC and areal BMD in a pilot study with adolescent and adult patients with thalassemia. Beneficial effect of WBV training, in terms of increased BMD and quadriceps strength, was also demonstrated in a study on patients with hemophilia [35].…”
Section: Effect Of Wbv Intervention In Other Groupsmentioning
confidence: 98%
“…Total body without head BMD increased. Högler et al [ 29 ] (2017) Randomized controlled trial 24 5–16 M + F WBV standing platform 20–25 Hz, 2–6 mm Twice daily (3 × 3 min) for 5 months No effect on bone mass Other groups Down syndrome Matute-Llorente et al [ 30 ] (2016) Randomized controlled trial 25 12–18 M + F WBV standing platform 25–30 Hz, 2 mm, 2.5–3.6 g 3 times per week with 10 repetitions of 10–20 s, for 20 weeks Positive effects on bone mass Obesity Tubic et al [ 12 ••] (2019) Randomized controlled trial 30 7–17 M + F WBV standing platform 16–24 Hz, 4 mm, 2.1–4.6 g 7–10 min, 3 days/week for 3 months No effect on bone mass, but effects for serum sclerostin Overweight Erceg et al [ 31 ] (2015) Randomized controlled trial 20 8–10 M WBV standing platform 30–40 Hz, low-high, 1.9–6.2 g 3 times per week with 10 repetitions of 30–60 s, for 10 weeks No effect on bone mass Anorexia nervosa DiVasta et al [ 32 ] (2017) Randomized double-blind trial 41 13–21 F WBV standing platform LMMS 32–37 Hz, 0.3 g 10 min/day during hospitalization of 5 days Prevents a decline in bone turnover during bed rest Idiopathic scoliosis Lam et al [ 33 ] (2013) Randomized controlled trial 149 15–25 F WBV standing platform LMMS 32–37 Hz, 0.3 g 20 min/day, 5 days/week for 12 months Positive effects on bone mass Thalassemia Fung et al [ 34 ] (2012) Longitudinal crossover pilot trial 18 10–18 M + F WBV standing platform LMMS 30 Hz, 0.3 g 20 min/day for 6 months Positive effects on bone mass ...…”
Section: Introductionmentioning
confidence: 99%